Percutaneous lovastatin accelerates bone healing but is associated with periosseous soft tissue inflammation in a canine tibial osteotomy model. Issue 2 (25th October 2013) - Bleedorn, Jason A.; Sullivan, Ruth; Lu, Yan; Nemke, Brett; Kalscheur, Vicki; Markel, Mark D.
ABSTRACT Experimental studies have shown the ability of statins to stimulate bone formation when delivered locally or in large oral doses, however most have been studied in rodents. This anabolic effect is through the selective activation of BMP‐2. Our purpose was to determine the effects of local treatment with lovastatin on bone healing in mammals as a preclinical animal model. We administered lovastatin (6 mg/kg) by percutaneous injection to a canine tibial osteotomy stabilized with external fixation. We found that lovastatin improved bone healing after a single injection into the fracture site assessed by serial radiography and histology at bone union. However, lovastatin treatment resulted in adverse local soft tissue inflammation. These results suggest that percutaneous lovastatin injection may be a useful adjuvant treatment over the course of bone healing to augment fracture repair, although further investigation into the mechanism of soft tissue adverse effects is warranted. © 2013 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:210–216, 2014.